Exodus from Privilege: Reflections on the Diaconate in Acts - BREIDENTHAL, Thomas E (Anglican theological review, 2013)
In the late nineteenth century the Episcopal Church routinely ordained men from ethnic minorities as permanent deacons for missionary work among their own people (David Pendleton Oakerhater being a prime example). First of all, we can talk about ordained ministry without having to import rank into our thinking about the church.